2023
DOI: 10.3390/math11010242
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Hyperparameter Fine-Tuning for Boosting the Robustness and Quality of the Particle Swarm Optimization Algorithm for Non-Linear RBF Neural Network Modelling and Its Applications

Abstract: A method is proposed for recognizing and predicting non-linear systems employing a radial basis function neural network (RBFNN) and robust hybrid particle swarm optimization (HPSO) approach. A PSO is coupled with a spiral-shaped mechanism (HPSO-SSM) to optimize the PSO performance by mitigating its constraints, such as sluggish convergence and the local minimum dilemma. Three advancements are incorporated into the hypothesized HPSO-SSM algorithms to achieve remarkable results. First, the diversity of the searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Recent studies aiming to increase the accuracy of the diagnosis systems indicate that hyperparameter optimization techniques proved powerful tools. In [21], a radial basis function neural network (RBFNN) designed to identify and diagnose non-linear systems is proposed. The hyperparameters of the RBFNN are computed using PSO-based techniques.…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…Recent studies aiming to increase the accuracy of the diagnosis systems indicate that hyperparameter optimization techniques proved powerful tools. In [21], a radial basis function neural network (RBFNN) designed to identify and diagnose non-linear systems is proposed. The hyperparameters of the RBFNN are computed using PSO-based techniques.…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…The results demonstrated that the proposed hybrid MLP-PSO classifier empowers practitioners to diagnose cardiovascular disease earlier, with enhanced accuracy and efficacy. An approach involving a radial basis function neural network (RBFNN) was proposed in [89], which was coupled with a robust hybrid particle swarm optimization (HPSO). The HPSO incorporated a spiral-shaped mechanism (HPSO-SSM) to enhance the PSO algorithm performance by addressing constraints such as slow convergence and the local minimum challenge.…”
Section: Significance Of Feature Selection In Cardiovascular Disease ...mentioning
confidence: 99%
“…Despite the initial success of using deep learning in clinical practice, challenges persist in recognizing multiple intersecting diseases and complex lesions, necessitating the development of additional DL-based techniques. These analytical undertakings encompass the identification of obstacles, the development of predictive models, and other vital elements that constitute the foundational components within the context of clinical intelligence-guided decisionmaking [32], [33], [34].…”
Section: Medical Research Heavily Relies On Medical Image Analysis a ...mentioning
confidence: 99%